ADVANCES AND LIMITATIONS IN CLINICAL MANIPULATIONS - NASRULLAH NASHTAR (International Journal of Multidisciplinary Research and Studies, 2021)
Selective serotonin reuptake inhibitors are among the neuronodulators that are utilised most frequently in the therapy of depression (SSRIs). The mechanism of action of SSRIs involves inhibiting the reabsorption of serotonin in the brain. This results in an increase in serotonin levels and, consequently, an improvement in mood. It may take several weeks for SSRIs to start working, and they may cause side effects such as nausea, sleeplessness, and sexual dysfunction in some individuals. Nonetheless, SSRIs have been demonstrated to be successful in treating depression in a significant number of people. Newer forms of antidepressants, including as serotonin-norepinephrine reuptake inhibitors (SNRIs) and atypical antidepressants, have been developed as a result of recent advancements in the therapeutic usage of neuronodulators for the treatment of depression. The mechanism of action of atypical antidepressants is distinct from that of SSRIs and SNRIs; these drugs work by inhibiting the reabsorption of both serotonin and norepinephrine. Some more recent antidepressants may have fewer adverse effects than previous antidepressants, in addition to their potential efficacy in the treatment of depression in certain patients.